Model for Enhancing the Competitiveness of the Food Industry and Urban Farming Business Community: A Case Study of the Kedaireka IRT–UM Grant - Setianingrum, Any; Nugroho, Randhy; Deviastri, Lily; Annisa, Intan Tri; Gani, Ariel Nian; Rofi'i, Muhammad; Nurhayati, Ely; Juhaeni, Ade Hilman; Supartoto, Supartoto (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Micro, Small, and Medium Enterprises (MSMEs) continue to face significant competitive pressures in an increasingly dynamic market environment, requiring sustainable and niche-based strategies to strengthen their competitiveness. This condition is experienced by CheekMe Mie Sehat, Kuliner Warteg Kalkul Bahari, and the Mustika Farmer Group (fostered partners of YARSI University) which have encountered business stagnation and difficulties in scaling up, particularly in product innovation, marketing, business governance, and compliance with quality standards. In response, a competitiveness enhancement model was developed and implemented through a combination of training and non-training interventions. The activities were conducted from November to December 2024 and included workshops, talk show sessions, certification assistance, laboratory testing, and the provision of digital and production infrastructure. The effectiveness of the program was evaluated using pre-test and post-test measurements, participant engagement, and observed improvements in business practices. The results indicate a measurable increase in participants’ knowledge, skills, and institutional capacity, demonstrating that an integrated and multidimensional approach can effectively enhance the competitiveness and sustainability of MSMEs in the food industry and urban farming sector.